Empowering The Communities in The Coastal Areas Of Lamongan East Java to Improve Their Welfare (Research, Society and Development, 2020)
East Java is a Province that has the potentials to grow and develop its Micro, Small, Medium Enterprises (Hence: MSMEs) in each of itscity/regency both located in the coastal and inland regions. The number of MSMEs in Indonesia is currently around 59.2 million (CNN Indonesia / Safir Makki). Three point seventy-nine (3.79) million of which have utilized the online platform in marketing their products, composing about about 8% of the total MSME entrepreneurs in Indonesia. In the digital era 4.0, of course, MSMEs entrepreneurs must also follow the current digital developments. The number of MSMEs in Lamongan City is 252,734 units. Some of these are based on the coastal areas, and they have enormous economic potentials,yet they have not yet grown optimally due to the constraints of management quality, access to funding, managerial models, business opportunities, and accessto information. For this reason, the researchers feel the urge to design an empowering model for the MSMEs in the coastal area communities to develop them more effectively as to foster the growth of MSMEs centers which are expected to contribute a lot to the local government, especially in Lamongan, East Java. The objectives of the research are: (a) identifying the characteristics of the community empowerment models (b) formulating a model of community empowerment to set up effective MSME centers (c) testing the effectiveness of community empowerment models in developing MSME centers (d) evaluating and refining the community empowerment models in developing MSME centers, and eventually formulating an effective management model for MSME centers in the coastal areas in East Java. The research makes use of a descriptive approach combined with quantitative methods. The object of the research is Brondong Village in Brondong District, Lamongan Regency. The results of this research reveal that the model of the community empowerment pattern in the MSME centers in Brondong Village in Brondong Lamongan District, in the coastal area of East Java is not yet effective, and that improvements in the aspects of community empowerment, household asset management, social interaction, institutions, and strategies for the community empowerment are imperative. And joint guidance and assistance from the local government, as well as its related agencies, and higher education institutions are necessary